REAL-TIME ONLINE QUALITY FEEDBACK SYSTEM BASED ON DIGITAL VISUALIZATION - Zhou, Zhiyong; Cao, Yinhai; Yang, Yang; Tang, Yongjin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Industry 4.0, initiated by Germany in 2013, focuses on digitization and process optimization in manufacturing. China’s ’Made in China 2025’ plan, aligned with Industry 4.0, was introduced in 2015. Motors are pivotal in industrial manufacturing, necessitating robust quality control. To enable real-time adjustments and enhance product quality, we propose an Online Quality Feedback (OQF) system using MySQL and big data. Implemented in H company’s motor production line, this system gathers real-time data from sensor-equipped stations, processes it through MySQL and big data analysis, and presents outcomes on a web interface. This empowers process and equipment engineers with concise insights for effective decision-making, ultimately improving the manufacturing process. Results affirm the effectiveness of our method in enhancing production management.